Plant protein consumption is associated with body mass index among women of reproductive age in Indonesia - Sistia, Fitra; Khusun, Helda; Februhartanty, Judhiastuty (Frontiers in Nutrition, 2023)
One of the known determinants of obesity in Southeast Asia countries, including Indonesia, is the nutritional transition, which is indicated by fast changes in food production, dietary habits, and physical activity. With rising incomes, plant protein from grains, tubers, and legumes is gradually being replaced by animal protein from poultry, eggs, dairy, and red meat . This change is identified as a protein transition. Different choices of protein sources in the diet have varying health effects. However, there is limited information on the Asian population on the role of protein consumption on the increasing obesity prevalence. Therefore, this study aimed to investigate the association of protein sources consumption with body mass index (BMI) among women of reproductive age in Indonesia. This study used secondary data from the 2018 Indonesia Food Barometer (IFB) conducted using a quantitative cross-sectional survey. A total of 467 Indonesian reproductive-aged women (20–49 years) were included in this study. Dietary intake, including protein consumption, was obtained using 24-hour dietary recall. Multiple linear regression was applied to find the association of protein consumption with BMI with a p-value ≤ 0.05 considered as a significant outcome variable. The Mean BMI was 25.02 kg/m2, median of animal and plant protein was 28.01 g/day and 25.37 g/day, respectively. Consumption of plant protein was significantly associated with BMI after adjusting for marital status and age (p-value = 0.043; R2=0.080). The quality of plant protein should be considered to prevent obesity problems among women of reproductive age.